PEMANFAATAN LIMBAH PUNTUNG ROKOK FILTER SEBAGAI BAHAN CAMPURAN BETON RINGAN BERPORI - Agata Iwan Candra; Edy Gardjito; Yosef Cahyo; Andri Dwi Cahyono; Zendy Bima Mahardana (U Karst, 2019)
Concrete is a vital component of construction. One of them is lightweight concrete consisting of a mixture of coarse aggregate, fine aggregate, cement which is united by water in a predetermined ratio. Lightweight concrete is concrete which has a weight of less than 2000kg / m³, lightweight concrete usually uses aggregate or lightweight material so that the concrete produced also has a light specific gravity. Waste cigarette filler waste is a waste that is difficult to recycle. Cotton filter cigarette butts are cotton-based fibers that are lightweight, porous and easily absorb water. For the use of this waste as a substitute for overall coarse aggregate, research needs to be carried out, namely the amount of compressive strength produced by replacing coarse aggregate from cigarette butts waste, job mix used according to SNI K-125 by completely replacing coarse aggregate with cigarette butts waste, Job mix for 1m³ concrete consists of 276 kg of cement, 214 liters of water, 148.62 kg of cigarette butts, and 828 kg of sand. From the above research, the highest compressive strength at 28 days reached K-115.56, which means that the target for concrete paving has reached K-100. As for the absorption, value is quite high from consecutive tests for ¼ hours, 1 hour, 4 hours, and 24 hours produced an average value of 0.116 liters, 0.269 liters, 0.374 liters, 0.699 liters. The results of the study of concrete density with a coarse aggregate of cigarette butts waste reached an average of 1831.11 kg / m³, for the study the pore figures yielded an average value of 0.2854, then the results of the porosity values obtained an average of 0.222016.                                                 AbstrakBeton merupakan komponen vital pada suatu konstruksi. Salah satunya beton ringan yang terdiri dari campuran agregat kasar, agregat halus, semen yang dipersatukan oleh air dengan perbandingan yang telah ditentukan. Beton ringan adalah beton yang memiliki berat kurang dari 2000kg/m³, beton ringan biasanya menggunakan agregat atau bahan yang ringan sehingga beton yang di hasilkan juga memiliki berat jenis yang ringan. Limbah puntung rokok fillter adalah suatu limbah yang sulit untuk di daur ulang. Puntung rokok fillter berbahan dasar kapas yang merupakan serat yang memiliki sifat ringan, berpori, dan mudah menyerap air. Untuk penggunaan limbah ini sebagai pengganti agregat kasar secara menyeluruh perlu diadakan  penelitian yaitu besarnya kuat tekan yang di hasilkan dengan penggantian agregat kasar dari limbah puntung rokok tersebut, job mix yang digunakan sesuai SNI K-125 dengan mengganti sepenuhnya agregat kasar dengan limbah puntung rokok,,job mix untuk 1m³ beton terdiri dari semen 276 Kg, air 214 liter, puntung rokok 148,62 Kg, dan pasir sebanyak 828 Kg. Dari penelitian di atas diperoleh nilai kuat tekan pada umur beton 28 hari tertinggi mencapai K-115,56 yang berarti telah mencapai target untuk paving beton sebesar  K-100. Sedangkan untuk nilai absorsinya cukup tinggi dari pengujian berturut-turut selama ¼ jam, 1 jam, 4 jam, dan 24 jam di hasilkan nilai rata-rata  sebesar 0,116 liter, 0,269 liter, 0,374 liter, 0,699 liter. Hasil penelitian dari berat jenis beton dengan agregat kasar limbah puntung rokok mencapai rata-rata 1831,11 Kg/m³, untuk penelitian angka pori di hasilkan nilai rata-rata mencapai 0,2854, selanjutnya hasil nilai porositas diperoleh rata-rata mencapai 0,222016.